Concentrations of total organic carbon, dissolved organic nitrogen, TOC/DON ratios, ammonium-nitrogen, nitrate-nitrogen, ammonium-N/nitrate-N ratios, and δ15 values of solution samples from a tropical montane forest in south Ecuador - Pablo Alvarez; Andre Velescu; Kerstin Pierick; Jürgen Homeier; Wolfgang Wilcke (PANGAEA, 2024)
We tested whether the δ15N values of total dissolved N (TDN), measured directly in solution with a TOC-IRMS, can be used to help elucidate N sources and sinks along the water path in a tropical montane forest in south Ecuador. The forest is located on the east-exposed slope of the eastern cordillera at 1850-2150 m above sea level and thus on the rim of the Amazon basin. We therefore collected rainfall, throughfall, stemflow, litter leachate, mineral soil solutions at the 0.15 and 0.30 m depths, streamflow, and fine litterfall samples in weekly resolution from January 2013 to December 2016. To obtain a sufficient N mass for the N isotope ratio analysis, we composited the weekly samples to quarterly ones. In addition to the ecosystem solutions, we also sampled leaves and roots of ten abundant tree species and horizons (the organic layer horizons Oi, Oe, Oa and the mineral soil horizons A and B) of 21 soil profiles. To assess a possible temporal change in the δ15N values of tree leaves, we analyzed a time series of two tree species (with five individuals per species) from 2008 to 2015. We determined the pH value, total organic C (TOC) and total N concentrations, and the δ15N values of total N in all samples. In the solutions, we additionally measured ammonium-N (NH4-N), nitrate-N (NO3-N), and dissolved organic N concentrations. Because of low N concentrations, δ15N values in rainfall and streamflow could not be measured in all samples. In such cases, we based the quarterly values on selected weekly samples that contained a TDN concentration of at least 1.4 mg/L. The δ15N values of total dissolved nitrogen changed markedly in the ecosystem solutions along the water path from rainfall through the forest to streamflow, which could be related to N sources, sinks, and transformations, while the temporal variation was less pronounced. The δ15N values of the solid phases helped in interpreting these changes. We conclude that the direct measurement of the δ15N values in TDN of ecosystem solutions provides a new straight-forward tool to detect changes in the N cycle of terrestrial ecosystems in high resolution.